SLIP SOURCE MODEL OF THE 1995 NEFTEGORSK EARTHQUAKE (NORTH SAKHALIN) FROM GEODETIC DATA - A. S. Prytkov; N. F. Vasilenko (Геодинамика и тектонофизика, 2023)
The May 27, 1995 Mw=7.0 Neftegorsk earthquake occurred in the north of Sakhalin Island, rupturing the Upper Piltun fault, a secondary feature of the main Hokkaido-Sakhalin regional fault zone. The fault geometry, coseismic slip model, and Coulomb stress changes in the earthquake focal area were calculated based on a finite fault modeling. We used near-field coseismic offsets at 24 points obtained by comparison between predating triangulation and GPS observations, which were collected before and after the earthquake. Our slip distribution model shows two major slip patches. Larger slip asperity (amplitude up to 6.36 m) was characterized by right-lateral strike-slip movements, which correspond to focal mechanism of the earthquake, whereas the northern segment has reverse fault mechanism with maximum slip of 2.64 m. The fault length and width, average slip and stress drop values are estimated at 78 km, 28 km, 1.91 m and 11.3 MPa, respectively. The estimated release moment is approximately 7.49×1019 N∙m equal to Mw=7.2, which is larger than that reported by the USGS and GCMT but consistent with the values reported by other researchers. The coseismic Coulomb stress changes enhanced the stress by more than 10 MPa on the southern segment of the Gyrgylaninsky fault and middle section of the Hokkaido–Sakhalin fault. Seismic risks on the nearest faults cannot be ignored in the future despite the fact that the earthquake with a magnitude of 5.8 occurred in 2010 near the Gyrgylaninsky fault. The recent GPS rates in the surroundings of the Neftegorsk surface rupture mean that the recurrence interval for similar earthquakes may be more than a thousand years.